2012
DOI: 10.1002/pd.3937
|View full text |Cite
|
Sign up to set email alerts
|

Fetal evaluation of the modified‐myocardial performance index in pregnancies complicated by diabetes

Abstract: In fetuses of DM mothers, evaluation of the Mod-MPI identifies those with worse maternal disease and large fetal size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 22 publications
2
39
2
Order By: Relevance
“…found that left ventricular MPI values of fetuses from gestational diabetic mothers were similar to those from pregestational diabetic mothers. In the same study, it was also reported that the MPI was significantly higher in the presence of insulin use . Our study revealed similar findings regarding the comparison between pregestational and gestational diabetes, but with conflicting results for insulin use.…”
Section: Discussionsupporting
confidence: 86%
“…found that left ventricular MPI values of fetuses from gestational diabetic mothers were similar to those from pregestational diabetic mothers. In the same study, it was also reported that the MPI was significantly higher in the presence of insulin use . Our study revealed similar findings regarding the comparison between pregestational and gestational diabetes, but with conflicting results for insulin use.…”
Section: Discussionsupporting
confidence: 86%
“…Figueroa et al . also demonstrated increased Mod‐MPI in fetuses of diabetic mothers compared with controls but the increase in MPI in their study (average Mod‐MPI of 0.42 in gestational diabetics and 0.45 in pregestational diabetics) was modest as compared with our study Their study group mostly comprised pregnant diabetics in the milder spectrum of disease.…”
Section: Discussioncontrasting
confidence: 93%
“…Increased MPI, suggesting impairment of global myocardial performance, has been reported in small numbers of fetuses of diabetic mothers in mid to late gestation . Figueroa et al . also demonstrated a modest increase in Mod‐MPI values in fetuses of diabetic mothers, but Mod‐MPI did not predict newborns with complications.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have proved abnormal maturation of cardiac functionality in the fetal age linked to structural alterations [18,19]. In the neonatal period, few data are available for cardiac functionality, probably because IDM with a good hemodynamic compensation are not subjected to routine tnEcho.…”
Section: Discussionmentioning
confidence: 99%